Төрийн алба дахь улс төрийн нөлөөллийн тухай ойлголт, онол, үзэл баримтлал, судалгааны харьцуулалт - Ц.Ганболд (Politology, 2017)
Independent administrative services are the institutional foundations of the contemporary state that, during the past 20 years, has gained prominence throughout Asia. The purpose of the article is to systematically examine the concept of political influence on public service, reviewing existing theory, research and the factors used to study.